Does being conceived by assisted reproductive technology influence adult quality of life? - Hammarberg Karin; Halliday Jane; Kennedy Joanne; Burgner David P.; Amor David J.; Doyle Lex W.; Juonala Markus; Ranganathan Sarath; Welsh Liam; Cheung Michael; McLachlan Robert; McBain John; et al. (TAYLOR & FRANCIS LTD, 2022)
Numerous studies have investigated the physical health and development of children and adolescents conceived with assisted reproductive technology (ART). Less is known about the quality of life of ART-conceived adults. This study explores the contributions of being conceived with ART and psychosocial cofactors present in young adulthood to the quality of life of adults aged 22-35 years. Young adults conceived through ART or natural conception (NC) completed questionnaires which included a standardized measure of quality of life (World Health Organization Quality of Life - Brief assessment (WHOQoL-BREF)) when aged 18-28 years (T1) and again when aged 22-35 years (T2). The WHOQoL-BREF has four domains: (i) Physical, (ii) Psychological, (iii) Social relationships and (iv) Environment. A total of 193 ART-conceived and 86 NC individuals completed both questionnaires. When accounting for other cofactors in multivariable analyses, being ART-conceived was strongly associated with higher scores (better quality of life) on the Social relationships, and Environment WHOQoL-BREF domains at T2. In addition, less psychological distress, a better relationship with parents, a better financial situation, and perceptions of being about the right weight at T1 were associated with higher scores on one or more of the WHOQoL-BREF domains at T2. In conclusion, being ART-conceived can confer advantages in quality of life in adulthood, independent of psychosocial cofactors.